An approach on microbial biosynthesis of L-glutaminase: a tumour inhibitor - Sunil Dutt P.L.N.S.N., Siddalingeshwara K.G, Karthic J, Mohsin S. Mushtaq, Naveen M Vishwanatha T and Prathiba K.S (Journal of Applied Pharmaceutical Science, 2013)
L-Glutaminase, an amidohydrolase enzyme has been a choice of interest in the treatment of lymphoblastic leukemia. This study investigates the production of extracellular L-glutaminase synthesis were carried out by using Aspergillus oryzae was evaluated under different fermentation parameters by employing submerged fermentation method. The L-glutaminase producers detected by the pink zone around the colony by simple plate assay method. Aspergillus oryzae S2 is the potential strain among the fungal isolates. The L-glutaminase synthesis were increased their yield after the optimization of fermentation parameters. The optimum pH 5.0, temperature 350C and inoculum size 1.0 ml and it showed 217.65 IU.
Keywords: L-glutaminase, fermentation kinetics, antitumour age